2004
DOI: 10.2298/vsp0402163m
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of intramammary arterial calcifications in diabetic women

Abstract: The obtained results supported the theory that intramammary arterial calcifications, detected by mammography, could serve as markers of co-existing diabetes mellitus and therefore should be specified in radiologic report in case of their early development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 4 publications
0
2
0
1
Order By: Relevance
“…Some studies show a significant association between BAC and hypertension, 19,32,33 whereas others show no such association. 4,24,34 Similarly, with diabetes mellitus, some studies show a statistically significant association, 6,19,35,36 whereas others show none. 4,24,37,38 …”
Section: Discussionmentioning
confidence: 98%
“…Some studies show a significant association between BAC and hypertension, 19,32,33 whereas others show no such association. 4,24,34 Similarly, with diabetes mellitus, some studies show a statistically significant association, 6,19,35,36 whereas others show none. 4,24,37,38 …”
Section: Discussionmentioning
confidence: 98%
“…In turn, Çetin et al 47 showed a 4-fold higher prevalence of BAC among patients with DM, suggesting BAC could be used to screen for DM in women aged ≥60 years. Similarly, Milosević et al 52 showed that BAC was found in 33.3% of type 1 DM, 40.2% of type 2 DM, and 8.2% of nondiabetics ( P = .0001). Age was not a significant covariable for the association between BAC and type 2 DM analysis, but there was a significant association between BAC and type 1 DM, especially in younger women ( P for trend = .001).…”
Section: Diabetes Mellitus and Bacmentioning
confidence: 80%
“…De manera similar, Milosevic et al expusieron que se encontraron calcificaciones vasculares en el 40.2% en las mamografías de pacientes diabéticas y el 8.2% en las mamografías de las paciones no diabéticas. La edad no fue una covariable significativa para la asociación entre calcificaciones vasculares intramamarias y diabetes mellitus tipo 2 13 . Debido a los estudios con resultados mixtos no se ha llegado a un consenso sobre la relación de la diabetes mellitus y las calcificaciones vasculares mamarias, ya que también se visualiza en pacientes de edad avanzada.…”
Section: Introductionunclassified